Itching Ears and Willing Learners: Balancing the Clarity and Complexity of Scripture - Barron, Bruce (Evangelical review of theology, 2022)
The popularity of the 'prosperity gospel', despite its tendencies toward simplistic and unbalanced theology, epitomizes one of the biggest problems in contemporary Christianity: how to provide adequately trained leaders for the global Christian movement, especially in the Majority World. This essay explores reasons why the problem exists, summarizes the contours of what all Christian leaders need to know, and identifies the Re-Forma organization cofounded by Manfred Kohl as a strategic solution.